miR-24-3p promotes cell migration and invasion by targeting TEL2 in nasopharyngeal carcinoma - Xiao, Bu-Fan; Xiong, Hui-Zhen; Wang, Wenjun; Huang, Zhaohao; Chen, Kaddie Kwok; Sang, Dan; Sang, Yi (Translational Cancer Research, 2018)
Background: miR-24-3p is a microRNA (miRNA) that is involved in the differentiation of various types of cancers and has been shown to act as an oncogene or tumor suppressor in certain cancers. However, the underlying mechanism of the miR-24-3p/TEL2 pathway has not been elucidated yet. Methods: The expression of miR-24-3p mRNA in NP69 cells and five NPC cell lines was detected. miR-24-3p mimics were transfected into S26 and 6-10B cells to explore the effect of miR-24-3p on the TEL2 mRNA and protein levels in NPC by Western blotting. In addition, tissue was collected from 116 patients with NPC, and total RNA was extracted for qRT-PCR to determine the expression of levels TEL2 and miR-24-3p. Furthermore, Transwell assays were conducted to study the effect of cancer cell migration and invasion. Results: In this study, we found that ectopic expression of miR-24-3p decreased the mRNA and protein levels of TEL2 in NPC cells, while knockdown of miR-24-3p increased the mRNA and protein levels of TEL2. Additionally, there was a negative correlation between miR-24-3p and TEL2 in NPC tissues. Mechanistically, we showed that miR-24-3p inhibits TEL2 expression via direct binding to the 3' untranslated region (3' UTR) of TEL2. Conclusions: Collectively, our results suggest that the miR-24-3p/TEL2 pathway may be a new target for treating patients with NPC.